Pengaruh Penggunaan Qris dan Strategi Marketing terhadap Keputusan Pembelian pada Toko Kurnia Jaya Sangatta Utara Kutai Timur - Riri Nilmalasari; Mustato Mustato; Moh Tauhid (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
This study aims to determine how much influence the Use of Qris and Marketing Strategy has on Purchasing Decisions at the Kurnia Jaya Store, Sangatta Utara, East Kutai. The variables used are the Use of Qris and Marketing Strategy as independent variables and Purchasing Decisions as dependent variables. This type of research is field research using a quantitative approach. This study uses data collection techniques that complement each other, namely the questionnaire technique to obtain research data by scoring from respondents. Observation techniques are also used to directly observe buying and selling activities at the Kurnia Jaya store, Sangatta Utara, then documentation techniques to obtain some supporting data that are also needed in this study. The sample of this study was 30 respondents who were consumers of the Kurnia Jaya Utara store using the quota sampling technique. Used by selecting respondents and data collection was carried out through the distribution of questionnaires. Furthermore, to analyze the data, the researcher used the multiple linear regression formula. From the results of the calculation using the formula above, the Use of Qris and Marketing Strategy obtained an R value = 0.857 with an interpretation between 0.800 - 1,000 which means that the correlation has a very strong effect. So the form of the regression equation is Y = 3.666 + 0.354 X₁ + 0.522 X₂ the regression equation is used to predict how much influence the use of Qris and Marketing Strategy has on purchasing decisions at the Kurnia Jaya Sangatta Utara store. After being calculated, the coefficient value of the determinant is 73.4%. This means that the independent variables of Qris Use (X1) and Marketing Strategy (X2) make a very strong contribution to the dependent variable of Purchasing Decisions (Y) while the remaining 26.6% is influenced by other factors that are not in the study.